Investments in small retention as a factor influencing land-use changes. A case study of Poland - Feltynowski, Marcin (Journal of Water and Land Development, 2023)
Building permit decisions are one of the most important elements of the investment process in Poland. It should be noted that water reservoirs influence the diversification of landscapes by increasing their attractiveness in both urban and rural areas. The article aimed to verify the relationship between the changes in land-use development and investments related to small retention. Another goal was classifying objects for which building permits have been obtained and registered. Changes in land-use development associated with the introduction of ponds, which blend in with the landscape, are desirable from the perspective of retaining water resources in urban and rural ecosystems. The research methodology was based on spatial data and included statistical analyses in three regions: Mazowieckie, Lodzkie and Swietokrzyskie. Studies carried out in these regions showed a spatial correlation associated with investments in small retention. The research used methods of the global I Moran statistic and local Moran statistics. The data used in the study came from the Register of Applications, Decisions and Notifications, made available by the Main Office of Construction Site. The research indicates clusters of investments in small retention in analysed regions. The majority of investors are residents who invest in earth ponds. The study shows that investment in small retention is connected with ecosystem services.